Special issue on language technology platforms. - Rehm, Georg; Piperidis, Stelios; Bontcheva, Kalina; Choukri, Khalid; Hajic, Jan (Language Resources & Evaluation, 2025)
The article discusses the organization and outcomes of the 1st International Workshop on Language Technology Platforms (IWLTP 2020), which was initially planned for May 2020 but was canceled due to the COVID-19 pandemic. Despite the cancellation, there was significant interest in the topic, leading to the publication of workshop proceedings and a subsequent call for papers for a special issue in the Language Resources and Evaluation Journal, focusing on Language Technology (LT) platforms and their interoperability. The special issue includes seven selected articles that explore various aspects of LT platforms, including infrastructure, user-centric development, and open-source solutions, highlighting the need for collaboration and standardization within the field.